Intention to Revisit Agrotourism: Effect of Service Quality and Visitor Experience - Imatul Hidayah; Abdul Wahid Muhaimin; Riyanti Isaskar (The University of Lampung, 2025)
Agrowisata Kebun Belimbing in Bojonegoro faced a decline in visitor numbers from 2021 to 2023. To increase visitor interest to return, the Agrotourism needs to enhance the quality of experiences that tourists receive and enjoy. This study aims to examine how service quality and visitor experience affect revisit intention, with satisfaction function as a mediating variable. The research employed explanatory quantitative method with a Structural Equation Modeling - Partial Least Square (SEM-PLS) approach. As many as 100 respondents who have visited the agrotourism was selected purposively. Data was collected through an online questionnaire and was analyzed using WarpPLS software. The results conclude that service quality and visitor experience directly affect visitor satisfaction significantly, with path coefficients of respectively 0.45 (p < 0.01) and 0.38 (p < 0.05). Both factors, however, did not directly affect on revisit intention, with path coefficients of 0.12 (p > 0.05) and 0.15 (p > 0.05), respectively. Visitor satisfaction, on the other hand, significantly influences revisit intention, with a path coefficient of 0.52 (p < 0.01), indicating that higher satisfaction increases the likelihood of revisiting the destination. Notably, service quality and visitor experience indirectly affect revisit intention through satisfaction, with effect sizes of 0.23 and 0.21, respectively.